2015
DOI: 10.1016/j.ijsu.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio (NLR) of five predicts 30-day morbidity in ruptured abdominal aortic aneurysms (rAAA): A retrospective cohort study

Abstract: A preoperative NLR >5 is an independent predictive marker of 30d morbidity in rAAAs. This appears to be in line with earlier literature demonstrating similar outcome in the elective group of abdominal aortic aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 21 publications
2
32
3
1
Order By: Relevance
“…Previous studies focused on the association between NLR value and poor clinical outcomes of type A aortic dissection or severe aortic events after TEVAR or open surgery. 17,18 In our study, we found signi cant difference of early outcomes between the high NLR group and low NLR group (adverse events, 17.3% vs. 5.4%, P = 0.005) despite that systemic in ammatory response of uTBAD is relatively lower than complicated aortic dissection or type A aortic dissection considering the lesion and comorbidities.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies focused on the association between NLR value and poor clinical outcomes of type A aortic dissection or severe aortic events after TEVAR or open surgery. 17,18 In our study, we found signi cant difference of early outcomes between the high NLR group and low NLR group (adverse events, 17.3% vs. 5.4%, P = 0.005) despite that systemic in ammatory response of uTBAD is relatively lower than complicated aortic dissection or type A aortic dissection considering the lesion and comorbidities.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, Jeong-ju et al [ 30 ] highlighted that a high NLR is an independent risk factor for poor prognosis in patients with primary cholangitis ( P < .01), and Lou et al [ 31 ] found that an NLR > 11 had important predictive value for the weaning failure of ICU patients ( P < .001). Zhou et al [ 32 ] has revealed that NLR > 6.5 often indicates the occurrence of a strangulated inguinal hernia in patients with inguinal hernia ( P < .001), and Ali et al [ 33 ] suggest that a preoperative NLR > 5 is an independent predictive marker of 30 day morbidity in ruptured abdominal aortic aneurysms ( P = .02).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies investigating the contribution of inflammation in the formation of aortic aneurysm and rupture pathogenesis (11,17). Sbarouni et al (11) compared NLR, PLR rates in patients with acute aortic dissection (AAD) with control patients consisting of uncomplicated aortic aneurysms and healthy volunteers in a study they conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Morello et al reported that WBC and platelet count will help in risk assessment of patients with low diagnosis probability in predicting AAD (18). Kordzadeh et al; reported that high NLR is an independent marker in predicting mortality in the first 30 days in cases with a ruptured abdominal aortic aneurysm (17). In our study, when compared to Group 1, it was found that the value of NLR (p = 0.029) was higher in Group 2 and this situation had a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%